Competence perspectives on resources, stakeholders and renewal - Sanchez, Ron; Heene, Aimé (Emerald, 2005)
The competence-based perspective on strategy and management emerged in the 1990s as a new approach to developing strategy and management theory and practice. In the past decade, the focus on organizational competences - and the resources, capabilities, and processes that create competences - has provided a highly productive broad church for theory development, research, and practice in both strategic and general management. Authored by a multidisciplinary group of scholars and practitioners working within the competence perspective, the papers in this volume contribute to developing a better theoretical and practical understanding of the role of resources, stakeholders, and organizational renewal in an organization's competences.The papers present both theoretical developments and empirical research based on a variety of case studies and other research in diverse industrial and geographical contexts. The papers in this volume are grouped under the three themes stated in the title of the volume. Part I includes papers that address a range of conceptual and practical questions about the role of both firm-specific and firm-addressable resources in an organization's competence building and leveraging, as well as issues in effectively managing a dynamic resource base. The papers in Part II investigate the management of stakeholders who provide the critical resources and capabilities a competent organization requires. Part III includes papers that focus on processes of organizational renewal, with an emphasis on the roles of key resources and stakeholders in contributing to renewal.
Keywords: Strategic planning.; elektronické knihy; electronic books